Observation on a colony of Bee-eater, Merops apiaster, in Marche Region - Niki Morganti; Francesca Portavia (Rivista Italiana di Ornitologia - Research in Ornithology, 2012)
The present study describes a Bee-eater, Merops apiaster, colony in the area of S. Costanzo municipality, Marche Region (N 43° 50’ E 13°10’). The area surrounding the historic breeding site, 3 cliffs within an old pliocenic sandstone quarry, is characterized by cultivations: Triticum spp. and Medicago sativa, mixed with Quercus pubescens and Robinia pseudoacacia small woods. Data from this research (2004 to 2007), continuing with the past studies, describe breeding trends and sites selection. The number of breeding pairs increased from 13 in 2004 to 39 in 2007, in accordance with general trends of this species in the wider area.